Alkali metal carbonate catalyzed copolymerization of anhydrides and epoxides: a simple, efficient and versatile approach to well-defined alternating polyesters. Issue 14 (17th March 2023) - Xie, Hongyan; Zheng, Lanlan; Feng, Jiabing; Wang, Xinyu; Kuang, Suping; Zhou, Li; Jiang, Jia; Xu, Yaling; Zhao, Yan; Xu, Zhiguang
Abstract : Readily available and economical alkali metal carbonates have been utilized to catalyze the ROAC of PA and various epoxides to afford polyesters with perfectly alternating sequence distribution, controlled molar masses, and moderate dispersity. Abstract : Ring-opening alternating copolymerization (ROAC) has recently become an attractive strategy for polyester synthesis. To date, ROAC catalysts have been restricted to organometallics and organic super-bases. In this work, we report ROAC using alkali metal carbonates (AMCs), one of the most common, simple, and inexpensive reagents in the laboratory, as efficient and environmentally benign catalysts. The ROAC of phthalate anhydride (PA) and propylene oxide (PO) can be catalyzed efficiently by AMC at 100 °C to afford polyesters with perfectly alternating structures. The structural and functional diversity of the resultant polyesters can be expanded by using various epoxide monomers and alcohol initiators. An alkali metal cation dissociated from the AMC successively activates the anhydride and the epoxide, and the carbonate anion activates the terminated hydroxyl. The cooperative catalysis accelerates the generation of the alternating structure.